2015
DOI: 10.1007/s00394-015-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in plasma and urine metabolites from Sprague–Dawley rats after oral administration of normal and high doses of hydroxytyrosol, hydroxytyrosol acetate, and DOPAC

Abstract: Our results suggest that different dosages of HT, HTA, and DOPAC do not provide a linear, dose-dependent plasma concentration or excretion in urine, both of which can be affected by the saturation of first-phase metabolic processes and intestinal transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 29 publications
3
63
1
Order By: Relevance
“…Many of these compounds derive from the breakdown pathways of the tyrosol group enriched in olives and/or the hippuric acid pathway, a pathway common to many classes of polyphenols. Both involve steps mediated by the gut microbiota and these catabolites and similar small phenolic acids have been reported to be excreted following ingestion of olive or olive fractions in previous studies [2022, 36, 37]. Few studies have reported the profile of metabolites present in fasted blood samples after chronic ingestion of olive pomace.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Many of these compounds derive from the breakdown pathways of the tyrosol group enriched in olives and/or the hippuric acid pathway, a pathway common to many classes of polyphenols. Both involve steps mediated by the gut microbiota and these catabolites and similar small phenolic acids have been reported to be excreted following ingestion of olive or olive fractions in previous studies [2022, 36, 37]. Few studies have reported the profile of metabolites present in fasted blood samples after chronic ingestion of olive pomace.…”
Section: Discussionmentioning
confidence: 90%
“…One recent study has shown that thyme phenolic compounds at different doses in olive oil can induce a small increase in bifidobacteria using the quantitative culture-independent method fluorescent in situ hybridization (FISH), with the suggestion that this change in microbiota could be related to improved LDL cholesterol oxidative status [21]. Similarly, a sex effect in terms of metabolism of HT and related compounds has been observed in rats with the suggestion that differential excretion of HT derivatives between male and female animals might be due to sex-linked differences in enterohepatic circulation [22]. However, no data are reported for differences in metabolism of these compounds between men and women or indeed, whether such differences if they do exist, could be due to sex-specific differences in gut microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…VOO phenolic compounds are mainly absorbed in the small intestine via passive diffusion, although absorption via intestinal membrane carriers might be also involved . Phenolic compounds that are not absorbed in the small intestine, such as secoiridoids, are degraded by the colonic microbiota …”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability of VOO phenolic compounds is affected by host factors, namely age and genomic profile, enzymatic activity, or colonic microflora . In addition, in animal studies gender appeared as a factor conditioning bioavailability of hydroxytyrosol derivatives, related with enterohepatic circulation, and longer persistence of metabolites in organisms …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation